PARTICULARITIES OF DRIVER’S WORK AND REST SCHEDULE CONDITIONS IN ORGANIZED CHILDREN CARRIAGE IN INTERCITY CONNECTION - O. E. Ianuchkova; M. R. Ianuchkov; N. V. Iakunina (Вестник СибАДИ, 2020)
Introduction. The article is devoted to the description of the shedule development particularities and a drivers’ work and rest schedule adjustment in an organized children carriage considering their age in an intercity connection. During the interurban transportation after first four hours and thirty minutes of uninterrupted driving, a special break for the rest is provided for drivers on the way lasting at least 45 minutes. This period can be divided into two or more parts, but the first part should last at least 15 minutes and the last one at least thirty minutes. At the same time children of different age groups perceive long distant travels variously due to their physiological development. The restriction of physical activity during a long time may have a negative impact on children’s physical and mental state. Children may have some problems with behavior control during long distant travels, it may lead to a travel rules violation, they remove their seat belts, start to walk around the bus, etc. The dependencies of the covered distance and time on a children’s age were identified based on the study results of the intercity children carriage process. The findings may be applied in a bus route timetables development, a drivers’ work and rest schedule adjustment during an organized children carriage in an intercity connection and also when planning transport infrastructure objects along popular tourist routes or frequently used transportation directions for students.The purpose of article is the description of a traffic schedule particularities development and a drivers’ work and rest schedule adjustment in an organized children carriage considering their age in an intercity connection. The scientific novelty lies in methodology used for a drivers’ work and rest schedule adjustment which depends on a distance and travel time in an organized children carriage by buses in an intercity connection and on the age of the carried children.Materials and techniques. While writing the article the methods of a passengers carriage theory, a statistical and systematic analysis, a transport process theory and also some other scientific methods and techniques were used.Results. The results have advisory nature and are proposed for use in a drivers’ work and rest schedule adjustment in an organized children carriage considering their age in an intercity connection.Discussion and conclusion. For the carriage of different aged children the scheme of traffic according to a children age group should be chosen. 4 age groups of children each of which correspond to a certain traffic and rest time on the way were identified during the study.